SUFISTIC APPROACH OF CHARACTER EDUCATION IN AN INDONESIAN ISLAMIC BOARDING SCHOOL - Hasibuan, Armyn; Mumtaz, Nadhif Muhammad; Anwar, Khairul; Haq, Moh Mansur Abdul; Nurjaman, Andri (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2025)
This article explores the role of Kiai leadership and management strategies in fostering character education at Islamic boarding schools, with a focus on the integration of Sufism as a spiritual approach to shaping students’ Islamic character (akhlak). Conducted at the At-Tamur Islamic Boarding School in Bandung, the study employs a qualitative method using interviews with the school’s director, a teacher, and alumni, alongside observations and documentation. Secondary data were drawn from scholarly articles, books, and other relevant literature. The findings reveal that the Kiai’s character education strategy is deeply rooted in Sufistic principles, emphasizing both hablu minallah (relationship with God) through weekly Friday night religious recitations, and hablu minannas (relationship with others) through active community service. The study contributes to the discourse on Islamic education by showcasing the practical application of Sufism in contemporary pesantren leadership.